Maxillary Necrosis: A Sequelae of Fungal Osteomyelitis - K Anbarasi; S Sathasivasubramanian; N Malathy; N Nandakumar; F Massillamani (Wolters Kluwer Medknow Publications, 2010)
Osteomyelitis is designated to a variety of bone diseases having inflammation as a common denominator. Persistent infection progresses to inflammation of marrow space, haversian system and periostium of affected region. Thrombosis of endothelial vessels cause necrosis and sequestrum formation. Both pyogenic and nonpyogenic infections of jaw lead to this condition. Immunosuppressed patients are more prone to mycelial infections, whereas their occurrence in immunocompetent individuals are highly unusual.